Gentamicin And Ciprofloxacin Sensitivity Against E. Coli Clinically Isolated From Urinary Tract Infection - AL-Khikani, Falah Hasan Obayes; Ahmeed, Haneen Waheed; Khudair, Khadeeja Kareem (Medical Science Journal for Advance Research, 2023)
Background: Escherichia coli (E. coli) is common bacteria that can be pathogenic and develop resistance to various antibiotics by different ways, making them difficult to treat with standard therapies. So monitoring antibiotic resistance is urgent. Material and methods: E. coli was isolated from urinary tract and cultured in three media (blood agar, macConkey agar, and EMB agar), then they were incubated for 24 hours at a temperature of 37oC to grow. The antibiotics discs (Ciprofloxacin, Gentamicin) were used by disc diffusion method. All the statistical analysis was done by using SPSS 26 software and Excel app. Results: The participants in this study were 70% women, while 30% were men with significant differences (P< 0.05). Gentamicin showed high rate of sensitivity (85%). The sensitive isolates to ciprofloxacin were 75%. Conclusions: We have found that 85% of bacteria are sensitive to gentamicin, and thus it can be used as an empirical treatment. Ciprofloxacin showed high rate of sensitivity against E. coli 75%.